Media, Gender, And Society: Relation of News Texts, Journalists Cognition, and Sociopolitical Context in Framing Female Politicians in Lombok Post Newspaper, Indonesia - Kadri Kadri (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2020)
This paper unveils the framing of female politicians in local newspapers published by Lombok Post, and relates to the cognition of journalists and the sociopolitical reality in the province of NTB. Anchored in the model of sociocognitive critical discourse analysis, this study discovered that the positive framing of female politicians in the newspaper was not inseparable from the provision of cordial relation between the journalist and female politician. The affirmative contents and cognition of the journalist regarding the female politicians were relevant to the sociopolitical context of the region depleted with the political racial identity and gender awareness of the community. Drawing on the empirical evidence, the domination of men in the editorial board of the mass media did not contribute to the presence of patriarchal news production in that good media relation built by the female politicians instead did minimize the news production policy that may be gender bias. This study demonstrates the importance of interpersonal communication competence and the maintenance of harmonious relation with the media and people for the sake of sustaining the positive image of female politicians constructed by mass media.